Interdisciplinary Collaboration: Pharmacists And Nutritionists Working Together For Patient Wellness (Journal of Namibian Studies : History Politics Culture, 2022)
This paper explores the concept of interdisciplinary collaboration between pharmacists and nutritionists to enhance patient wellness. The collaboration between these two healthcare professionals offers a comprehensive approach to addressing patients' health needs by integrating medication management with dietary and lifestyle interventions. By leveraging their respective expertise, pharmacists and nutritionists can conduct thorough patient assessments, optimize medication therapy, provide education and counseling, foster continuity of care, and promote preventive health measures. This collaborative model emphasizes personalized care tailored to individual needs, empowering patients to make informed decisions about their health.